Is Percutaneous Endoscopic Gastrostomy A Solution for Aspiration Pneumonia, or Just An Illusion? - Yüksel, Aycan; Esendağlı, Dorina; Nezalzova, Polina; Ulubay, Gaye (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Aspiration pneumonia is a pulmonary infection that occurs when food, liquid, saliva, or vomit is aspirated into the lungs. Percutaneous enteral gastrostomy (PEG) prevents aspiration pneumonia while ensuring the patient receives adequate nutrition. The authors aimed to evaluate the incidence and risk factors of post-PEG aspiration pneumonia. Materials and Methods: Elderly patients who underwent PEG between January 2019 and December 2023 were included in this retrospective study. The incidence of aspiration pneumonia was compared between the periods before and after PEG. Mortality rates and risk factors of post-PEG aspiration pneumonia were investigated. Results: A total of 430 out of 534 patients who underwent PEG were included. The aspiration pneumonia rate was 30.1% (n = 133) before PEG and 21.9% (n = 94) after PEG (P = .003). The 1-year mortality rate of post-PEG aspiration pneumonia was 58.5% (n = 55). Age ≥ 80 years (OR: 3.11; 95% CI, 1.12-8.76), home residency (OR: 3.31; 95% CI, 0.99-10.8), discontinuation of primary caregiver who had been trained about PEG (OR: 5.8; 95% CI, 1.4-25.2), chronic lung disease (OR: 3.016; 95% CI, 1.17-7.77), history of recurrent aspiration pneumonia prior to PEG (OR: 3.401; 95% CI, 1.073-10.779), spending ≥20 hours of the day in supine position (OR: 6.512; 95% CI, 1.879-28.103), requiring PEG due to stroke (OR: 2.46; 95% CI, 1.062-5.69), and esophagus cancer (OR: 3.047; 95% CI, 1.174-8.88) were associated with post-PEG aspiration pneumonia. Conclusion: Percutaneous enteral gastrostomy reduces aspiration pneumonia in general, but there remain risks, particularly in patients with stroke or esophageal cancer. Supine position and discontinuation of primary caregiver who had been trained about PEG are major risk factors. Cite this article as: Yüksel A, Esendağlı D, Nezalzova P, Ulubay G. Is percutaneous endoscopic gastrostomy a solution for aspiration pneumonia, or just an illusion? Turk J Gastroenterol. 2025;36(9):609-617.